Parental responses to public investments in children: Evidence from a maximum class size rule - Peter Fredriksson; Björn Öckert; Hessel Oosterbeek (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2015)
We study differential parental responses to variation in class size induced by a maximum class size rule in Swedish schools. In response to an increase in class size: (i) only high-income parents help their children more with homework; (ii) all parents are more likely to move their child to another school; and (iii) only low-income children find their teachers harder to follow when taught in a larger class. These findings indicate that public and private investments in children are substitutes, and help explain why the negative effect of class size on achievement in our data is concentrated among low-income children.
Keywords: I21; I28; J24; C31; 330; class size; parental responses; social background; regression discontinuity